Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.14730/aaps.2022.00430
|View full text |Cite
|
Sign up to set email alerts
|

What factors during elective rotations influence undergraduates to pursue plastic surgery as a career?

Abstract: Background Plastic surgery is considered one of the most competitive specialties globally. In Saudi Arabia, it was established in 2001 in the central province (Riyadh) and then expanded in 2009 to include more eastern and western provinces. Previous research has identified several factors that impact pursuing a career in plastic surgery.Methods This cross-sectional study was conducted through a five-page, five-section questionnaire distributed among senior medical students and interns using online platforms be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…These results are consistent with other studies that have found that learning experiences in RSSs help medical students define their professional future. [8][9][10][11][12] According to Schmidt, 13 Al-Nojaidi, 14 Jabaiti et al 15 and Lee, 16 RSSs provide medical students with a vision of the professional lifestyle of a surgeon and the technical skills required in each surgical specialty. If the vision of a surgical career aligns with the interests of medical students, it can be used as a persuasive argument to encourage them to enrol in a surgical residency.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with other studies that have found that learning experiences in RSSs help medical students define their professional future. [8][9][10][11][12] According to Schmidt, 13 Al-Nojaidi, 14 Jabaiti et al 15 and Lee, 16 RSSs provide medical students with a vision of the professional lifestyle of a surgeon and the technical skills required in each surgical specialty. If the vision of a surgical career aligns with the interests of medical students, it can be used as a persuasive argument to encourage them to enrol in a surgical residency.…”
Section: Discussionmentioning
confidence: 99%